Identifying novel Sea Lamprey (Petromyzon marinus) spawning areas in a large unimpounded river system - Lowe, Michael R.; Jubar, Aaron K.; Barber, Jessica M.; Hondorp, Darryl W.; Holbrook, Christopher M. (Frontiers in Freshwater Science, 2025)
IntroductionDespite the success of the Sea Lamprey Control Program (SLCP) in reducing Sea Lamprey (Petromyzon marinus) abundance throughout the Laurentian Great Lakes, control remains a significant challenge in the Saint Clair-Detroit River System (SCDRS) due to the system's size, flow dynamics, and amount of potentially suitable spawning habitat.MethodsWe used acoustic telemetry to identify repeated patterns in habitat use, presumed spawning areas, and migratory routes for 271 acoustic-tagged Sea Lamprey in the SCDRS during the 2016 and 2017 spawning seasons.ResultsSixty-nine percent of tagged Sea Lamprey appeared to spawn in the Saint Clair River with many individuals displaying commonly shared movement histories in terms of timing and channel use. Probable spawning locations were associated with the main river channel upstream of major bifurcations (e.g., Stag and Fawn Islands) in the Saint Clair River and overlapped with areas of high bottom flow.DiscussionSelection for low flow refugia during migration appears water temperature dependent. Traditional control methods are likely to be inefficient in the SCDRS, highlighting the need for novel supplemental strategies tailored to large river systems.